PENGARUH LAMA PERENDAMAN BIJI SENGON (Paraserianthes falcataria) MENGGUNAKAN AIR DAUN SIRIH (Piper betle Linn.) TERHADAP KUALITAS BENIH - Zulkarnain, Tika; Yoza, Defri; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Paraserianthes falcataria are fast growing trees in the tropical and has many benefits economically. In order to avoid seeds of Paraserianthes falcataria not decrease the quality of seeds during storage. Seed treatment is necessary to keep the seeds able to survive until the time of planting by using Piper betle Linn. leaf as an antiseptic and disinfectant. The purpose of this study to determine the effect of submursion seeds in water Piper betle Linn. leaf on the quality of seed germination and to know the optimum time to submursion seeds in water  Piper betle Linn. leaf to maintain the quality of seeds Paraserianthes falcataria. This research was conducted by using completely randomized design (CRD), which consists of 4 treatments and 4 replications. Treatment consists of: P10 = Submursion seeds Paraserianthes falcataria use Piper betle Linn. leaf water for 10 minutes; P20 = Submursion seeds Paraserianthes falcataria use Piper betle Linn. leaf water for 20 minutes; P30 = Submursion seeds Paraserianthes falcataria use Piper betle Linn. leaf water for 30 minutes; P40 = Submursion seeds Paraserianthes falcataria use Piper betle Linn. leaf water for 40 minutes. Research has shown that submursion seeds with water Piper betle Linn. leaf is able to improve the quality of seeds Paraserianthes falcataria during storage and the optimal time of submursion seeds for 30 minutes is the best treatment on seed germination percentage (62%), speed seed germinated (3.05 days), and increase seedling height (6.44 cm).   Keywords :  Paraserianthes falcataria, Piper betle Linn., Seed quality.